The Expression of Adolescents’ Delinquent Behaviour at School - Padgurskytė, Vaida (Jaunųjų mokslininkų darbai, 2018)
Adolescence is a very important period in a person’s life. The wish to become an independent personality becomes a priority that is pursued in various ways – acceptable and contradictory to society’s norms and standards. However, every adolescent can hardly distinguish proper behaviour and actions from harmful ones. The youths want to try everything in order to understand what society expects from them and what they expect from themselves. School is the second social environment (after the family) where an adolescent’s behaviour reflects what is being taught in the family, what values are transmitted to a newly formed personality.With the help of scientific researches we may prove that delinquent adolescents’ behaviour, its expressions, problems are especially acute research problems for Lithuanian and foreign researchers. Having carried out the research, we found out that there is a big variety of expressions of delinquent behaviour at school. Summarising the results of the survey we may state that smoking, bullying, uncensored vocabulary, conflicts among pupils, harassment of younger pupils, aspiration to dominate among adolescents are frequent phenomena in modern school, therefore, these facts cause concern in reference to the behaviour of certain pupils in an educational environment. However, the majority of questioned pupils stated that they behave properly, pay much attention to studies and do not have time for inappropriate activities.
Keywords: adolescent; delinquent behaviour; school